Effect of electrospinning process variables on the size of polymer fibers and bead-on-string structures established with a 23 factorial design - Korycka, Paulina; Mirek, Adam; Kramek-Romanowska, Katarzyna; Grzeczkowicz, Marcin; Lewińska, Dorota (Beilstein Journal of Nanotechnology, 2018)
This work examines the effect of selected process parameters on the diameter of uniform and heterogeneous fibers (with and without bead-on-string structures) and the size of beads obtained during the electrospinning process. A 23 factorial design was performed to determine the influence of the following factors: electrical voltage, flow rate and dynamic viscosity of the poly(vinylpyrrolidone) ethanolic solution. Factorial design enables the analysis of the mathematical relationship between the chosen factors and the response with a minimum number of experiments. The factor having the most significant impact on the size of beaded fibers and beads was the solution viscosity, while the voltage had the greatest influence on the bead-free fiber diameter. The interactions between the studied factors were also analyzed. It was found that the presented method can be used for the design of an optimal and cost-effective electrospinning process, allowing the desired product to be obtained with expected features.
Keywords: bead-on-string structure; electrospinning; factorial design; polymer fiber